Isolation of Cronobacter sakazakii from different herbal teas - Stojanović Marija M.; Katić Vera; Kuzmanović Jelena (Vojnosanitetski Pregled)
Bacground/Aim. Cronobacter sakazakii (C. sakazakii) is an emerging food-borne pathogen that has increasingly raised interest among the whole public community and food industry, especially in the production of powder infant formula. It has been isolated from water, sediment and soil. The question is whether this pathogen can be present in herbal teas. Herbal teas are widely used for great number of health problems, as an additional or sometimes only “medicine” given. The aim of this study was to investigate the presence of C. sakazakii in herbal teas which are traditionally used for all restricted populations, including newborns and immunocompromised infant and adults. Methods. In this study 150 samples of dried herbal teas were tested: Children (Baby) tea (11), Althaea officinalis (7), Sennae folium (4), Mentha piperita (8), Hypericum perforatum (3), Thymus serpyllum (5), Matricaria recutita (6), Fruit tea (18), Black, Green and Rooibos tea (11), Salvia officinalis (9), Arctostaphylos uva ursi (5), Urtica dioica (3), Achillea millefolium (2), Melissa officinalis (4), Cynosbati fructus (3), Flower Herbal tea (3) and 17 different mixtures of tea (48 samples). The presence of C. sakazakii was also investigated in previously positive samples of prepared teas (48 samples) after 2 h, 12 h and 24 h. C. sakazakii was isolated by the use of the official method ISO TS 22964 : 2006 and confirmed with the biochemical test API 20E (Biomerieux-France). Results. The obtained results showed that C. sakazakii was isolated from 48 (32%) samples dried herbal teas. C. sakazakii was not isolated only from 2 (4%) of the 48 tested samples of prepared tea and in 46 (96%) of the samples C. sakazakii remained viable after 2 h, 12 h and 24 h. Conclusion. Herbal teas should be carefully used, especially for infants and immunocompromited people with severe chronic diseases because of the possibility of infection by C. sakazakii. Better control and improve testing as well as new facts about this pathogen are necessarry.